Vibrational Spectra, Electronic Structure and Properties of the Molecules Aspirin and Ibuprofen. - Ejuh, Geh Wilson; Ndikilar, Chifu Ebenezar; Nya, F. Tchangnwa; Samuel, Nouemo; Marie, Ndjaka Jean (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The FT-IR Vibrational spectra analysis, electronic structures and properties of the anti-inflammatory drugs Aspirin and Ibuprofen in gas and water and ethanol have been studied by using ab initio and DFT computational calculation. The present investigation deals with the analysis of structural and bonding features responsible for biological activities, stability of the molecules, average polarizability, anisotropy, energies and the IR vibrational spectra of the molecules. The observed and the calculated vibrational frequencies are found to be in good agreement. The experimental FT-IR spectra also coincide satisfactorily with those of the theoretically constructed line spectra at the B3LYp/6-31+G* level of theory.